2006
DOI: 10.24266/0738-2898-24.4.185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dolomitic Lime Rate and Application Method on Substrate pH and Creeping Woodsorrel Establishment

Abstract: Experiments were conducted to evaluate the effect of dolomitic lime rate and application method on substrate pH, creeping woodsorrel (Oxalis corniculata) establishment in containers, and growth of azalea (Rhododendron ‘Rosebud’) and pieris (Pieris japonica ‘Claventine’). In Experiments 1 and 2, pulverized dolomitic limestone was incorporated at 0, 6, 12, 24, or 47 kg/m3 (0, 10, 20, 40, or 80 lbs/yd3). Containers were overseeded with twenty seeds of creeping woodsorrel. Substrate pH was measured with a pour-thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This volumetric water gradient can also affect other chemical and biological properties as greater moisture affects decomposition processes [26], mineral nutrient release from controlled release fertilizers [27], and gas emissions from the substrate [28]. Wada et al [29] showed decreasing substrate pH in containers from the surface to the container bottom and attributed the higher pH near the substrate surface to irrigation water alkalinity having greater effect on the substrate surface than deeper in the container. Jeong et al [30] also reported stratification of pH and EC through the container profile; however, they reported the opposite trend with pH increasing from the top to the bottom while EC decreased.…”
Section: Substrate Stratificationmentioning
confidence: 99%
“…This volumetric water gradient can also affect other chemical and biological properties as greater moisture affects decomposition processes [26], mineral nutrient release from controlled release fertilizers [27], and gas emissions from the substrate [28]. Wada et al [29] showed decreasing substrate pH in containers from the surface to the container bottom and attributed the higher pH near the substrate surface to irrigation water alkalinity having greater effect on the substrate surface than deeper in the container. Jeong et al [30] also reported stratification of pH and EC through the container profile; however, they reported the opposite trend with pH increasing from the top to the bottom while EC decreased.…”
Section: Substrate Stratificationmentioning
confidence: 99%
“…The mechanisms underlying possible seedbank regulation by soil pH are unclear, but could include toxicity from aluminum or other heavy metals, or changes in the fungal:bacterial ratio of the soil microbial community that affect seed decay (Pakeman et al 2012). Soil pH can also affect the quantity of seed inputs to the soil by affecting growth and subsequent seed production in some weed species (Wada et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, pH and EC (the primary parameters measured from pour-through extracts) form an electrochemical gradient within the vertical profile of the container. Wada et al (2006) showed decreasing substrate pH in containers from the surface to the container bottom and attributed the higher pH near the substrate surface to alkalinity of surface applied irrigation water having greater effect on the substrate surface than lower in the container. Jeong et al (2012) reported the opposite trend, with pH increasing from the top to the bottom, whereas EC decreased.…”
mentioning
confidence: 99%